Birth, coming of age and death: The intriguing life of long noncoding RNAs. (July 2018) - Samudyata,; Castelo-Branco, Gonçalo; Bonetti, Alessandro
Abstract: Mammalian genomes are pervasively transcribed, with long noncoding RNAs being the most abundant fraction. Recent studies have highlighted the central role played by these transcripts in several physiological and pathological processes. Despite several metabolic features shared between coding and noncoding transcripts, these two classes of RNAs exhibit multiple differences regarding their biogenesis and processing. Here we review such distinctions, focusing on the unique features of specific long noncoding RNAs.